2016
DOI: 10.5500/wjt.v6.i4.712
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of estimated glomerular filtration rate in kidney transplantation from deceased donors with acute kidney injuries

Abstract: AIMTo evaluate and compare the outcomes of kidney transplant (KT) from deceased donors among standard criteria, acute kidney injury (AKI) and expanded criteria donors (ECDs).METHODSThis retrospective study included 111 deceased donor kidney transplant recipients (DDKT). Deceased donors were classified as standard criteria donor (SCD), AKI donor and ECD. AKI was diagnosed and classified based on change of serum Cr by acute kidney injury network (AKIN) criteria. Primary outcome was one-year estimated glomerular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Our preliminary 1-year results were in agreement with other reports and were subsequently confirmed by two smaller studies. 21,22 Our current results with complete follow-up beyond the first year are consistent with the U.K. kidney transplant report by Boffa et al regarding long-term outcomes. 23 While the Standard Transplant Analysis and Research file from the Organ Procurement and Transplantation Network (OPTN) does not provide serial serum creatinines, the U.K.…”
Section: Discussionsupporting
confidence: 91%
“…Our preliminary 1-year results were in agreement with other reports and were subsequently confirmed by two smaller studies. 21,22 Our current results with complete follow-up beyond the first year are consistent with the U.K. kidney transplant report by Boffa et al regarding long-term outcomes. 23 While the Standard Transplant Analysis and Research file from the Organ Procurement and Transplantation Network (OPTN) does not provide serial serum creatinines, the U.K.…”
Section: Discussionsupporting
confidence: 91%
“…Data from 17 studies [ 14 , 20 22 , 24 , 29 33 , 35 , 37 , 38 , 40 , 41 , 44 , 46 ] reporting acute rejection was pooled. The results show no significant difference in the odds of acute rejection between donor AKI vs. non-AKI kidneys groups (OR 1.29, 95% CI = 0.97–1.71, I 2 = 76%, Z = 1.75, p = 0.08).…”
Section: Resultsmentioning
confidence: 99%
“…14 studies [ 14 , 19 22 , 28 30 , 35 , 37 , 39 , 43 45 ] reported the eGFR at 12 or more months post-renal transplantation. The pooled results show similar eGFR levels between the AKI and non-AKI populations (WMD = −2.09, 95% CI = −3.56 to 0.62, I 2 = 41%, Z = 2.79, p = 0.05) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 1428 citations identified from the electronic and hand searches, 123 full-text articles were identified for possible eligibility, and after exclusion, 33 single-center studies, 8 , 12 , 27 57 four multicenter studies, 5 , 58 60 and seven registry-based studies 7 , 11 , 13 , 61 64 were included in the meta-analysis (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%